2013
DOI: 10.1101/gr.154328.112
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the fate of colistin resistance and Acinetobacter baumannii during patient treatment

Abstract: Bacterial whole-genome sequencing (WGS) of human pathogens has provided unprecedented insights into the evolution of antibiotic resistance. Most studies have focused on identification of resistance mutations, leaving one to speculate on the fate of these mutants once the antibiotic selective pressure is removed. We performed WGS on longitudinal isolates of Acinetobacter baumannii from patients undergoing colistin treatment, and upon subsequent drug withdrawal. In each of the four patients, colistin resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 45 publications
(52 reference statements)
2
90
0
2
Order By: Relevance
“…The colistinresistant mutants had a colistin MIC of Ն64 g/ml. Rapid development of colistin resistance in some bacterial species has previously been reported (12,17,18). A previous mutant prevention concentration study also indicated that colistin resistance can be readily induced during drug therapy by single-step mutation in A. baumannii, P. aeruginosa, and K. pneumoniae (19).…”
mentioning
confidence: 88%
“…The colistinresistant mutants had a colistin MIC of Ն64 g/ml. Rapid development of colistin resistance in some bacterial species has previously been reported (12,17,18). A previous mutant prevention concentration study also indicated that colistin resistance can be readily induced during drug therapy by single-step mutation in A. baumannii, P. aeruginosa, and K. pneumoniae (19).…”
mentioning
confidence: 88%
“…Adams et al [40] Park et al [41] Lesho et al [42] Beceiro et al [44] Rolain et al [46] Kim et al [48] Arroyo et al [34] Snitkin et al [47] Choi et al [43] Choi et al [45] Colistin resistance and dependence in A. baumannii sule polysaccharide (CPS) and efflux pumps [54,55]. For CPS production, reduced production of CPS in colistin-resistant mutants was observed in Klebsiella pneumoniae, which is a contradictory finding [56].…”
Section: P233s A)mentioning
confidence: 99%
“…Genomic sequencing revealed comprehensive drug-resistance mechanisms, such as a 41.6-kb closely related antibiotic resistance island in the chromosome (Huang et al, 2012), the horizontally transmittable carbapenem resistance gene (bla ) containing a plasmid (in isolate MDR-TJ, with 454 Titanium) among different A. baumannii strains (Huang et al, 2012;Lee et al, 2013), a list of antimicrobial resistance-associated genes (with 454 and SOLiD) (Rolain et al, 2013), a diversified resistance gene list (with Illumina Hiseq2000) (Tan et al, 2013), and longitudinally evolved antibiotic resistance gene mutations and mutational pathways under pressure from the antibiotic colistin (with 454 Titanium) (Snitkin et al, 2013). Since its invention by Rothberg et al (2011), Ion Torrent sequencing technology has been successfully applied to complete genomic sequencing, such as in Clostridium sp.…”
Section: Whole Genome Sequencing Is a Feasible Way To Investigate Thementioning
confidence: 99%